Feasibility of Utilizing PREMM Score for Lynch Syndrome Identification in an Urban, Minority Patient Population. (May 2021) - Adviento, Brigid; Conner, Michael; Sarkisian, Alexander; Walano, Nicolette; Andersson, Hans; Karlitz, Jordan
The PREMM5 model is a web-based clinical prediction algorithm that estimates the gene-specific risk of an individual carrying a Lynch syndrome germline mutation based on targeted family history questions. The objectives of our study were to determine the feasibility of screening for LS in an urban, minority patient population in a primary care setting using the PREMM5 model and characterize patient barriers associated with difficulty completing the questions. Participants were recruited from Tulane Internal Medicine primary care clinics on 9 random collection dates. Our data illustrates the difficulty patients have in recalling important details necessary to answer the PREMM questionnaire.